Down the Victorian data mine - Hanley, James; Turner, Elizabeth (Significance (Oxford, England), 2024)
Abstract We tend to think of data mining as having originated in the late twentieth century, prompted in large part by e-commerce. But, here, James Hanley and Elizabeth Turner tell the story of an eighteenth-century customer loyalty programme later “quarried” for a 1884 article whose statistical ingenuity and overreach won it international media reaction